ANALISIS KEBIJAKAN PEMELIHARAAN MESIN DALAM RANGKA MEMINIMUMKAN BIAYA PEMELIHARAAN PADA PT PARAMOUNT BED INDONESIA - Rully, Tutus; Putri, Carolina Feronika (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
ABSTRACTThis study aimed to describe how the engine maintenance performed by PT Indonesia Paramount Bed inminimizing the cost of maintenance pasa press machine. The Research was about on engine maintenance inminimizing the cost of maintenance at PT. Paramount Bed Indonesia by using quantitative data and datasources that used are primary and secondary. The method of analysis that used in the study is the case studymethod. The company has been doing engine maintenance in accordance with the existing theory. But themaintenance of the company is not optimal because pasa production process still occurs frequently stopedengine suddenly. Therefore, companies should evaluate the maintenance periodically to the next productionrun properly and damage to the product that occurs can be less.Keywords: Maintenance of the machine and the Minimum Cost